Redescription of the females of Hystrignathus rigidus Leidy, 1850 (Nematoda: Hystrignathidae), parasites of Odontotaenius disjunctus (Coleoptera: Passalidae) from eastern USA - Morffe, Jans; García, Nayla; Davis, Andrew K. (Zootaxa, 2015)
The female of Hystrignathus rigidus Leidy, 1850 (Nematoda: Hystrignathidae) is redescribed on the basis of new material from Odontotaenius disjunctus (Coleoptera: Passalidae) from Athens, Georgia, USA; which also constitutes a new locality record. SEM images are provided for the first time for the species. It is also first shown that H. rigidus presents ridged-shelled eggs. A differential diagnosis is provided. H. rigidus can be differentiated from the rest of the species of this genus by having a short, non inflated first cephalic annule; spines that surpass the level of the oesophagus, an absence of lateral alae, ridged-shelled eggs and its length of the body and tail. The material from the present study differs from a previous redescription by Christie (1934) by its shorter body (2.125–2.950 vs. 2.130–4.200), first cephalic annule (0.003–0.005 vs. 0.012) and oesophagus (0.350–0.430 vs. 0.650–0.670).